Melanoma-specific bcl-2 promotes a protumoral M2-like phenotype by tumor-associated macrophages. Issue 1 (7th April 2020) - Di Martile, Marta; Farini, Valentina; Consonni, Francesca Maria; Trisciuoglio, Daniela; Desideri, Marianna; Valentini, Elisabetta; D'Aguanno, Simona; Tupone, Maria Grazia; Buglioni, Simonetta; Ercolani, Cristiana; Gallo, Enzo; Amadio, Bruno; et al.
Abstract : Background: A bidirectional crosstalk between tumor cells and the surrounding microenvironment contributes to tumor progression and response to therapy. Our previous studies have demonstrated that bcl-2 affects melanoma progression and regulates the tumor microenvironment. The aim of this study was to evaluate whether bcl-2 expression in melanoma cells could influence tumor-promoting functions of tumor-associated macrophages, a major constituent of the tumor microenvironment that affects anticancer immunity favoring tumor progression. Methods: THP-1 monocytic cells, monocyte-derived macrophages and melanoma cells expressing different levels of bcl-2 protein were used. ELISA, qRT-PCR and Western blot analyses were used to evaluate macrophage polarization markers and protein expression levels. Chromatin immunoprecipitation assay was performed to evaluate transcription factor recruitment at specific promoters. Boyden chamber was used for migration experiments. Cytofluorimetric and immunohistochemical analyses were carried out to evaluate infiltrating macrophages and T cells in melanoma specimens from patients or mice. Results: Higher production of tumor-promoting and chemotactic factors, and M2-polarized activation was observed when macrophages were exposed to culture media from melanoma cells overexpressing bcl-2, while bcl-2 silencing in melanoma cells inhibited the M2 macrophage polarization. In agreement, the number of melanoma-infiltrating macrophages in vivo was increased, in parallel with a greater expression of bcl-2 in tumor cells. Tumor-derived interleukin-1β has been identified as the effector cytokine of bcl-2-dependent macrophage reprogramming, according to reduced tumor growth, decreased number of M2-polarized tumor-associated macrophages and increased number of infiltrating CD4 + IFNγ + and CD8 + IFNγ + effector T lymphocytes, which we observed in response to in vivo treatment with the IL-1 receptor antagonist kineret. Finally, in tumor specimens from patients with melanoma, high bcl-2 expression correlated with increased infiltration of M2-polarized CD163 + macrophages, hence supporting the clinical relevance of the crosstalk between tumor cells and microenvironment. Conclusions: Taken together, our results show that melanoma-specific bcl-2 controls an IL-1β-driven axis of macrophage diversion that establishes tumor microenvironmental conditions favoring melanoma development. Interfering with this pathway might provide novel therapeutic strategies.